THE EFFECT OF COOPERATION AND INNOVATION CAPABILITY ON INNOVATION TYPE OF THE EXPORT ORIENTED SME’S IN INDONESIA - Elan Nurhadi Purwanto; Titus Indrajaya (Yayasan Education and Social Center, 2022)
The unit of analysis is export-oriented SMEs located in Bali, Jakarta, West Java, East Java and Central Java. The SMEs in question are not differentiated based on the type or production sector, because the authors are of the view that the factors examined in this study can apply in general to all SMEs. The research observation unit is the manager of each SME’s. The manager in question is the top manager or top manager of the company. Furthermore, the number of samples in the study was calculated from a total population of 317 SMEs. Based on the Slovin formula, 176 samples were obtained. The results of this study are, The innovation capability model for export-oriented SMEs in Indonesia is supported by implementing of cooperation, Cooperation that is implemented by export-oriented SMEs include factors of vertical cooperations and horizontal cooperations. The dominant role is horizontal partnerships, namely partnerships implemented with partners in educational institutions or business incubators, financial institutions, government institutions or related agencies, as well as with associations or industrial communities or exporters, and so forth. Innovation capability in export-oriented SMEs includes the dimensions of strategic capability, network capability, process capability, and learning capability. These four dimensions of capability have an important role for SMEs so that SMEs have the capability to be able to produce types of innovation within their companies. The dominant role is network capability and strategy. The types of innovation produced by export-oriented SMEs include product innovation, marketing innovation, and process innovation. The dominant types of innovation are marketing innovation and process innovation